Tinjauan Hukum Pidana terhadap Kebijakan Keamanan di Perumahan Berdasarkan Peraturan Perumahan: Studi tentang Tanggung Jawab Pengelola dan Hak Warga - Ramadan Prabowo; Muhammad Ridwan Lubis (Jurnal Begawan Hukum (JBH), 2025)
Housing, as a basic human necessity, demands not only physical comfort but also assurance of safety and legal protection for its residents. In recent years, the rise in security violations within residential areas has raised serious concerns, especially regarding the authority of housing management and the frequent neglect of residents’ rights. Various security policies such as 24-hour gate security, CCTV installation, and visitor access restrictions are often enforced without a clear legal basis and without the participation of residents, thereby creating the potential for legal violations, including those related to criminal law and human rights. This study aims to analyze the forms of criminal liability that may be imposed on housing management in cases of negligence or abuse of authority in the implementation of security policies. It also examines the forms of legal protection available to residents and identifies potential criminal law violations arising from such policies. The research adopts a normative and empirical juridical approach, with a case study conducted at DL Sitorus I Housing Complex in Simalungun Regency. The results of the study show that the security policies at DL Sitorus I lack a valid internal legal foundation, were not developed through participatory means, and are not supported by standardized operating procedures (SOPs). This situation creates room for overreach by security personnel, such as arbitrary detention of visitors and unauthorized interrogations, which may violate Article 333 of the Indonesian Penal Code. Management may be held indirectly criminally liable under the principles of culpa in vigilando (negligence in supervision) and culpa in eligendo (negligence in the selection of personnel). The study recommends the formulation of internal regulations based on resident participation and the provision of legal training for security officers to ensure a fair, transparent, and legally compliant residential security system that upholds the principles of criminal law and human rights protection.